The Changes of Lipidomic Profiles Reveal Therapeutic Effects of Exenatide in Patients With Type 2 Diabetes - Zhang, Lin; Hu, Yanjin; An, Yu; Wang, Qiu; Liu, Jia; Wang, Guang (Frontiers in Endocrinology, 2022)
Objective: Exenatide has been demonstrated beneficial effects on patients with type 2 diabetes mellitus (T2DM) regarding lipid metabolism. However, the potential mechanism remains unclear. We used a lipidomic approach to evaluate lipid changes in response to treatment with exenatide in T2DM patients. Methods: Serum lipidomic profiles of 35 newly diagnosed T2DM patients (before and after exenatide treatment) and 20 age-matched healthy controls were analyzed by ultrahigh-performance liquid chromatography-tandem quadrupole time-of-flight mass spectrometry. Results: A total of 45 lipid species including sphingomyelins (SMs), ceramides (CERs), lysophosphatidylcholines (LPCs), phosphatidylethanolamines (PEs), lysophosphatidylethanolamines (LPEs) and phosphatidylcholines (PCs) were identified in all participants. Compared to the healthy controls, 13 lipid species [SM (d18:1/18:0, d18:1/18:1), Cer (d18:1/18:0, d18:1/16:0, d18:1/20:0, d18:1/24:1), LPC (15:0, 16:0, 17:0), PC (19:0/19:0), LPE (18:0) and PE (16:0/22:6, 18:0/22:6)] were markedly increased in the T2DM group, while PE (17:0/17:0) and PC (18:1/18:0) were decreased (P < 0.05). The serum SM (d18:1/18:0, d18:1/18:1), LPC (16:0), and LPE (18:0) were significantly decreased after exenatide treatment, which was accompanied by the amelioration of lipids and glycemic parameters (TC, LDL-C, ApoA-I, FCP and HbA1c) in T2DM patients. The chord diagrams showed distinct correlation patterns between lipid classes and subclasses among healthy controls, T2DM patients before and after exenatide treatment. Conclusion: Our results revealed that the therapeutic benefits of exenatide on T2DM might be involved in the improved lipid metabolism, especially SM, LPC, and LPE. Clinical Trial Registration Number: NCT03297879.